Longer-term growth prospects for CESEE - Josef Schreiner (Oesterreichische Nationalbank (OeNB), 2022)
In light of the profound changes that both the European economy and European politics have experienced since the global financial crisis of 2008, this policy paper intends to retrace the experience of Central, Eastern and Southeastern European (CESEE) countries with transition and catching-up over the past 20 years. A special focus shall be put on impediments for potential growth and the impact of mega trends on future convergence. The CESEE region under discussion here comprises the EU Member States from the enlargement rounds of 2004, 2007 and 2013, candidates and potential candidates for EU membership on the Western Balkans as well as Ukraine and Russia.
Keywords: 330; Wirtschaftswachstum; Wirtschaftliche Konvergenz; Wirtschaftsprognose; Transformationsstaaten; Mitteleuropa; Osteuropa; Südosteuropa